Laboratory testing for cytomegalovirus among pregnant women in the United States: a retrospective study using administrative claims data - Leung Jessica (BMC Infectious Diseases, 2012)
Abstract Background Routine cytomegalovirus (CMV) screening during pregnancy is not recommended in the United States and the extent to which it is performed is unknown. Using a medical claims database, we computed rates of CMV-specific testing among pregnant women. Methods We used medical claims from the 2009 Truven Health MarketScan® Commercial databases. We computed CMV-specific testing rates using CPT codes. Results We identified 77,773 pregnant women, of whom 1,668 (2%) had a claim for CMV-specific testing. CMV-specific testing was significantly associated with older age, Northeast or urban residence, and a diagnostic code for mononucleosis. We identified 44 women with a diagnostic code for mononucleosis, of whom 14% had CMV-specific testing. Conclusions Few pregnant women had CMV-specific testing, suggesting that screening for CMV infection during pregnancy is not commonly performed. In the absence of national surveillance for CMV infections during pregnancy, healthcare claims are a potential source for monitoring practices of CMV-specific testing.